Dark triad, sociosexual orientation, and mate preferences in short and long-term relationships – Exploratory study. (October 2021) - Marcinkowska, Urszula M.; Brewer, Gayle; Jaremba, Agata; Jones, Imogen; Payne, Elin; Lyons, Minna T.
Abstract: Some partner preferences are universal, while others show a pronounced inter-individual variation. As both Dark Triad and sociosexuality play an important role in mate choice, this study measured how inter-individual variation in these traits relate to preferred mate characteristics over two mating conditions. Participants ( N  = 419, M age = 20.62, SD  = 4.27) completed an on-line survey on mate preferences, short Dark Triad measure, and sociosexuality inventory (SOI Attitude, Behaviour and Desire). Narcissism in women correlated with most demands (e.g., good financial prospects) in both short and long-term relationships. Machiavellianism in women correlated with preferring long and short-term partners with financial prospects, and short-term partners with favourable social status. Psychopathy in women had a negative association with several preferences (e.g., desire for children), but only in long-term context. The only significant correlation in men was between narcissism and preference for favourable social status in long-term partners. In both sexes and across both mating contexts chastity correlated negatively with sociosexual attitude. We also found a number of significant, negative correlations between sociosexual attitude and mate preferences in women (e.g., similar religion, desire for children).